Psychological Impact of COVID-19 Epidemic on Adolescents: A Large Sample Study in China - Zhou, Jiawei; Wang, Yini; Bu, Tianyi; Zhang, Sijia; Chu, Haiyun; Li, Jiarui; He, Jingyun; Zhang, Yansheng; Liu, Xuan; Qiao, Zhengxue; Yang, Xiuxian; Yang, Yanjie (Frontiers in Psychiatry, 2021)
Background: The COVID-19 pandemic is a major public health emergency. However, little is known about the psychological impact of this pandemic on adolescents. We aim to assess the prevalence and influencing factors of depression, anxiety, and posttraumatic growth (PTG) among adolescents in a large sample study. Methods: This cross-sectional study collected demographic data and mental health measurements from 175,416 adolescents covering 31 provinces, centrally administered municipalities, and autonomous regions in mainland China from February 23 to March 8, 2020. The status of depression, anxiety, and PTG was assessed by the nine-item Patient Health Questionnaire, seven-item generalized anxiety disorder questionnaire, and post-traumatic growth inventory. Results: The prevalence of depression, anxiety, and PTG in adolescents was 35.9, 28.0, and 45.6%, respectively. The prevalence of depression and anxiety in the slight or severe epidemic areas was similar. Regression analysis showed that female sex and older age were associated with higher levels of depression, anxiety, and lower levels of PTG. Symptoms related to COVID-19, excessive attention to epidemic information, living in urban or severe epidemic areas, and conflicts with parents during home quarantine were risk factors for depression, anxiety, and PTG. Frequent communication with peers, exercise, and receiving public welfare psychological assistance were protective factors. Poor family economic status was a significant risk factor for depression and PTG. Conclusion: Our findings suggested that positive and negative psychological reactions coexist in adolescents faced with the pandemic. The factors associated with psychological problems and PTG provide strategic guidance for maintaining adolescents' mental health in China and worldwide during any pandemic such as COVID-19.